(untitled) (Scientific journal of the Fergana State University, 2025)
Currently, the population of our country is increasing by 1 million people annually. This naturally leads to an increased demand for all types of activities, including housing. As a result, many residential buildings are being constructed nowadays. However, the question of their durability concerns all of us. The purpose of our research is to identify the differences and advantages of construction materials between regions. In this study, we tested five different types of construction materials exclusively from Bukhara and Kashkadarya regions. This is because it is essential today to determine the strength of materials, such as bricks, that meet standards, both for humanity and for manufacturing enterprises. The ability of our buildings to withstand earthquakes and vibrations directly depends on the quality of the raw materials used in construction, as well as the type of raw materials from which the products are made. Based on the research results using fired bricks as an example, the products of Kashkadarya region proved to be relatively stronger than those of Bukhara region. The reason for this is the higher salinity levels in Bukhara region, which can lead to the faster deterioration of brick products. In this research, we used the compression method to measure deformation with the help of an alpha test device. The results of our study showed that the outcomes for both regions were satisfactory.